ANALISIS GAYA HIDUP HEDONISME DI ERA GLOBALISASI MAHASISWA UIN RADEN FATAH PALEMBANG - Seftiana, Afil Fres; Syafitri, Adesta; Eliyati, Eliyati; Ningsih, Lisa Septia; Jadidah, Ines Tasya (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
The aim of this research is to find out how the hedonistic lifestyle changes in the era of globalization among students at Uin Raden Fatah Palembang. This research is descriptive qualitative research because it takes an approach that examines the hedonistic life among students at Uin Raden Fatah Palembang. The data collection technique was carried out by interviews with administrators and students of Uin Raden Fatah Palembang and the analysis we obtained. By using this research, we can collect information to answer research problems, provide in-depth and comprehensive understanding according to the object being researched and also become a challenge in itself because the influence of hedonism in this era of globalization can bring positive or negative results for UIN Raden Fatah students, Palembang. The end of this research is that the researcher knows that there is a change in the Hedonistic lifestyle among UIN Raden Fatah Palembang students. The hedonistic style is also influenced by several factors, namely internal and external. One of the biggest supporting factors is external factors involving reference groups. It is from this reference group that hedonistic behavior can emerge if we cannot restrain and limit ourselves.